Multi-objective optimization of dynamic construction site layout using BIM and GIS. (15th July 2022) - Zavari, Masoud; Shahhosseini, Vahid; Ardeshir, Abdollah; Sebt, Mohammad Hassan
Abstract: Construction site layout planning (CSLP) refers to the facilities' placement in the site boundaries by optimizing layout objectives and considering constraints. This study aims to provide a framework for optimizing the construction site layout dynamically, utilizing information from Building Information Modeling (BIM) and Geospatial Information System (GIS). The framework arranges temporary facilities within the site boundaries by considering a multi-objective optimization problem for minimizing the total on-site travel distance of personnel and equipment between facilities and enhancing the safety level of the construction site. Since a good site layout would increase the safety level of the construction site, facilities are placed based on the proximity relationships among them, which represent the planner preference in locating the facilities near or far from one another due to safety concerns. Then, the Guided Population Archive Whale Optimization Algorithm (GPAWOA) is applied for solving the problem. The contribution of this study includes developing a more realistic model using BIM and GIS together for acquiring the spatial data, navigating dynamically, and considering available indoor and outdoor space continuously. Accordingly, a plugin is developed to find the optimum construction site layout using the ArcGIS APIs and Microsoft C#. Finally, an illustrative case is considered to validate the practicality and functionality of the suggested framework. The results depict that employing the proposed method decreases about 20% of the total on-site traveling distance. Additionally, it results in a safer facilities arrangement regarding the proximity preference, compared with conventional methods. Highlights: A practical method for construction site layout planning that uses BIM and GIS is proposed. This method considers all available indoor and outdoor spaces for facilities allocation. GPAWOA is applied for optimizing the multi-objective site layout problem. The efficiency and functionality of the proposed method are demonstrated in a case.